Advances in natural products and antibody drugs for SLE: new therapeutic ideas - Han, Yibing; Liu, Lingwei; Zang, Bo; Liang, Ruiwen; Zhao, Xinyue; Liu, Bin (Frontiers in Pharmacology, 2023)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune systemic disease with a wide range of clinical symptoms, complex development processes, and uncertain prognosis. The clinical treatment of SLE is mainly based on hormones and immunosuppressants. Research on novel therapy strategies for SLE has flourished in recent years, especially the emergence of new targeted drugs and natural products that can modulate related symptoms. This review discusses the current experience including B-cell targeted drugs (belimumab, tabalumab, blisibimod, atacicept, rituximab, ofatumumab, ocrelizumab, obexelimab, and epratuzumab), T-cell targeted drugs (abatacept, dapirolizumab, and inhibitor of syk and CaMKIV), cytokines targeted drugs (anifrolumab and sifalimumab), and natural products (curcumin, oleuropein, punicalagin, sulforaphane, icariin, apigenin, and resveratrol). The aim of this paper is to combine the existing in vitro and in vivo models and clinical research results to summarize the efficacy and mechanism of natural drugs and targeted drugs in SLE for the reference and consideration of researchers.